Material and Imaging Analysis Procedure for the Investigation of Paintings in the Archbishop’s Palace of Seville - Javier Moreno-Soto; Anabelle Križnar; Francisco José Ager; Auxiliadora Gómez; Antonio Gamero-Osuna; Agustín Martín-de-Soto; Miguel Ángel Respaldiza (Heritage, 2023)
The Archbishop’s Palace of Seville harbours an important art collection with mostly works by great Renaissance and Baroque artists. However, the authorship of some paintings is unknown, and, in a few cases, there is an interest in discovering the painter due to the quality of the artwork. As a first step for this purpose, a systematic analysis procedure has been established using non-destructive techniques, such as UV photography and IR reflectography, to locate interventions and underpaintings, as well as X-ray fluorescence to identify original pigments and those of later interventions. The study following this established protocol is presented with the example of two paintings by unknown authors. They were made in different centuries representing, consequently, different styles. UV images showed several retouches, while IR reflectography revealed under-drawing and composition corrections (pentimenti). Furthermore, XRF identified the pigments applied in the production of the different colours and tonalities, allowing to characterise the artist’s palette, whose pigments generally agree with the dates when the artworks were produced. This study resulted in valuable information on painting materials and techniques, which will be useful in the search for authorships, among others.